2015
DOI: 10.1016/j.oooo.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported oral health, oral hygiene, and oral HPV infection in at-risk women in Ho Chi Minh City, Vietnam

Abstract: Objectives This study aimed to examine the relationship between self-reported oral health, oral hygiene practices, and oral human papillomavirus (HPV) infection among women at risk for sexually transmitted infections in Ho Chi Minh City, Vietnam. Study design Convenience and referral sampling methods were used in a clinic-based setting to recruit 126 women aged 18–45 years between August–October 2013. Behavioral factors were self-reported. Oral-rinse samples were tested for HPV DNA of two low-risk and 13 hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The aetiology and risk factors of oral and oropharyngeal HPV infection remains controversial; however, past studies have shown that these risk factors include oral sex, multiple sexual partners, poor oral hygiene and immunodeficiency conditions [15,16,17,18,19,20]. Identifying key risk factors may help to improve disease screening processes to identify high-risk individuals for developing OPC which may lead to OPC prevention and improve disease mortality [21]. …”
Section: Introductionmentioning
confidence: 99%
“…The aetiology and risk factors of oral and oropharyngeal HPV infection remains controversial; however, past studies have shown that these risk factors include oral sex, multiple sexual partners, poor oral hygiene and immunodeficiency conditions [15,16,17,18,19,20]. Identifying key risk factors may help to improve disease screening processes to identify high-risk individuals for developing OPC which may lead to OPC prevention and improve disease mortality [21]. …”
Section: Introductionmentioning
confidence: 99%
“…In Mexican males we obtained a prevalence of 34% while reported data ranged from 10.1% (7) to 20% in male attending in a STD clinic (11). In Mexican female we obtained a prevalence of 36.3%, higher than reported in the 2009-2010 USA National Health Survey: 3.6% (6,9).…”
Section: Discussionmentioning
confidence: 62%
“…We obtained a prevalence of 34.5% for all HPV subtypes. HPV prevalence reported in scientific literature is wide, ranging from 0.67% reported in Chinese (5); 6.9%-16% in Americans (6,), to 24.6% in Vietnamese (7). This data suggest that Mexican population possesses the highest oral HPV prevalence reported.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, women are reportedly at risk of this infection apart from much susceptible male in places like Vietnam [9]. Some estimates suggest that 70-90% of new oropharyngeal cancers have evidence of HPV [10].…”
Section: Discussionmentioning
confidence: 99%